A Review of the Features and Efficacy of Chat-GPT AI Writing Assistant in Influencing EFL Learners’ English Writing Skills - Xiong, Yuanyuan (Transactions on Social Science, Education and Humanities Research, 2024)
In today's digital age, the growing use of AI-driven tools in language acquisition, especially for English writing, calls for more investigation. Grasping the impact of advanced technologies such as Chatbot Generative Pre-trained Transformer (Chat-GPT) on the learning of English as a Foreign Language (EFL) is crucial for both educators and researchers. Consequently, the objective of this study is to investigate how Chat-GPT, in its role as an AI writing assistant, influences the writing abilities and performance of EFL students. Utilizing Constructivism theory, this research delves into the characteristics and effectiveness of Chat-GPT in improving the writing abilities, performance, motivation, engagement, self-regulation, and self-efficacy of EFL students in English writing. A review of existing literature indicates that Chat-GPT's attributes, such as smart tutoring, interactive tutoring, an investigative learning setting, and automated writing assessment systems, play a major role in enhancing students' writing abilities and creating a supportive educational atmosphere. Additionally, the research underscores the beneficial impact of Chat-GPT on the writing abilities of students. To sum up, the research highlights the significance of incorporating AI-driven tools such as Chat-GPT into language education methods and underscores the necessity for future studies to fully understand their role in improving the writing skills of EFL students.